2016
DOI: 10.1186/s12879-016-1954-8
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and correlates of herpes simplex virus type 2 infection among young adults in Arkhangelsk, Northwest Russia: a population-based cross-sectional study

Abstract: BackgroundHerpes simplex virus type 2 (HSV-2) infection is the most common cause of genital ulcer disease (GUD) worldwide. Mother to child transmission causes high morbidity and mortality among infants. Russia is on the brink of a generalized HIV-epidemic, but Arkhangelsk is still a low-prevalence area. HSV-2 infection is associated with a three-fold increased risk of HIV-infection. The evidence on the seroprevalence of HSV-2 in Russia is limited. The aim of this study was to assess HSV-2 seroprevalence and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Those who agreed to participate presented themselves at the University Clinic of the Northern State Medical University (NSMU) of Arkhangelsk to complete a self-administered questionnaire and provide a blood sample. The enrollment procedure was described previously in detail [ 15 ]. Data collection lasted from the end of September 2010 until June 2011.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Those who agreed to participate presented themselves at the University Clinic of the Northern State Medical University (NSMU) of Arkhangelsk to complete a self-administered questionnaire and provide a blood sample. The enrollment procedure was described previously in detail [ 15 ]. Data collection lasted from the end of September 2010 until June 2011.…”
Section: Methodsmentioning
confidence: 99%
“…We then categorized these responses as low (1–4), medium (5–7), and high (8–10) income. The description of most variables can be found elsewhere [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The variable "knowing someone with hepatitis C" was divided into "no", "yes", and "do not know". The description of other variables used in this study can be found elsewhere [17].…”
Section: Description Of the Variablesmentioning
confidence: 99%
“…19 Titania et al conducted a study which included 1243 adults and found significant association with up to five sex partners. 7 2 out of 3 Adolescents reporting multiple partners in this study were HIV positive as in Table 5. These numbers may be small but indicate the need to address vulnerable populations through education, monitoring and counseling.…”
Section: Number Of Sexual Partnersmentioning
confidence: 99%